If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 68 = 2l + (12 + 2w) Remove parenthesis around (12 + 2w) 68 = 2l + 12 + 2w Reorder the terms: 68 = 12 + 2l + 2w Solving 68 = 12 + 2l + 2w Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-2l' to each side of the equation. 68 + -2l = 12 + 2l + -2l + 2w Combine like terms: 2l + -2l = 0 68 + -2l = 12 + 0 + 2w 68 + -2l = 12 + 2w Add '-68' to each side of the equation. 68 + -68 + -2l = 12 + -68 + 2w Combine like terms: 68 + -68 = 0 0 + -2l = 12 + -68 + 2w -2l = 12 + -68 + 2w Combine like terms: 12 + -68 = -56 -2l = -56 + 2w Divide each side by '-2'. l = 28 + -1w Simplifying l = 28 + -1w
| 3(k+8)+3=2k-7 | | 0.3*0.9= | | 5(x+2)+3=6(3x+9)-2 | | 5Xv-18-4=-36 | | 1/2k-3=-9x-4 | | 4/5=10/3x | | 3/4x-2/3=7/12 | | 3x^2-42x+135=0 | | 4/5=10/3 | | 1-9/5x3 | | -8g+10=-10-12g | | x+-4=-15 | | X=4(1)+8 | | p-25/140=12/42 | | 15/16x=11 | | 4x^2(x^2+6xy-7y^2)=x | | .6(x+8)-.8(5x+2)=10 | | 3/7/6 | | 2x+2(3x+4)=8+8x | | -4x^2+3=-6 | | 12=-r+11 | | (6x+7)-29=6x | | -3(2x+1)+x=2-(4x-2) | | 9x-10y=-13 | | 1/4(-8g+24)=g | | 5v-4-6=15+4v | | 4x+14=11x-2 | | 2x+63=9 | | ((1/t)-1)/(t-1) | | 7(4n+4)-10= | | -40n-43=3n | | 8n+8(n+7)=-35+3n |